A single amino acid change within the R2 domain of the VvMYB5b transcription factor modulates affinity for protein partners and target promoters selectivity - Hichri, Imène; Bogs, Jochen (BMC plant biology, 2011)
Flavonoid pathway is spatially and temporally controlled during plant development and the transcriptional regulation of the structural genes is mostly orchestrated by a ternary protein complex that involves three classes of transcription factors (R2-R3-MYB, bHLH and WDR). In grapevine (Vitis vinifera L.), several MYB transcription factors have been identified but the interactions with their putative bHLH partners to regulate specific branches of the flavonoid pathway are still poorly understood.